(untitled) (Architecture Image Studies, 2025)
Purpose The research will attempt to formulate an integrated ecological economic feedback model that will describe the dynamics of the pastoral economy in Xilingol long-term. It researches on the interaction of grassland biomass, livestock population behavior, household economic choices, and policy interventions via strengthening and balancing feedbacks. The aim is to find leverage points to ecological sustainability and produce the regional system of intelligence that can predict the risk of degradation and lead to adaptive governance. Methodology/approach: The study uses a system dynamics modeling technique whereby ecological, economical; climatic and policy subsystems are integrated into a cohesive feedback mechanism. The calibration is done with the help of empirical data in the form of NDVI records, livestock census, climatic records, and government policy archives. Stock-flow frameworks, nonlinear models, degradation limits are developed to determine the four scenarios in 30 years of continuation and intensification of grazing: continuity with baseline, increased grazing, and rotated grazing; continuity with intensity increase of subsidies. Validation involves historical fit test, sensitivity test, structural test, and extreme condition test. Originality/Relevance: Even though many studies are currently carried out on grassland degradation or pastoral household behaviour, few of them combine ecological, economic, and institutional processes in the same dynamic framework. The article provides a new ecological-economic feedback reproduction that is specific to Xilingol and locates it in a regional intelligence paradigm. It is a predictive, feedback-sensitive instrument, which gives the policy makers an opportunity to anticipate the potential ecological dangers in the long term and assess the unintended impacts of interventions like subsidies or stocking limits. Key findings: Findings have shown that the pastoral economy is controlled by connected reinforcing and balancing loops, which generate overshoot-and-collapse dynamics. Ecological thresholds are traversed gradually yet permanently under both baseline and intensified grazing conditions and cause decreased biomass, low livestock productivity, unpredictable income and eventual system instability. Rotational grazing retains biomass at 92-97% original values and stabilizes the size of the herd. The intensification of subsidies increases the short-term income and enhances the incentives of herd expansion at the expense of degradation acceleration in case ecological constraints are not considered. Theoretical/methodological contributions The article contributes to the ecological-economic systems theory by showing the combination of delayed feedbacks, nonlinear ecological reactions and economic incentives in the formation of pastoral trajectories. It is methodologically adaptable in bringing ecological processes, household decision behavior and policy instruments together in one structure of system dynamics, which provide a base to the intelligence of the environment in regions. The model is useful in that it can identify the mechanisms of policy resistance early, detecting them beforehand, and the framework is replicable across the analysis of pastoral SES in other areas.